The Perception of Students from the Economic Area on the New Learning Methods in the Knowledge Society - Nicoleta Dospinescu; Maria Tătăruşanu; Gina Ionela Butnaru; Lucian Berechet (Amfiteatru Economic Journal, 2011)
The competition that exists among the higher education institutions involves great efforts to adapt to the new requirements of the modern society. The educational offers must face the new challenges that require flexibility, rapidity, complexity and provide students both with specific habits and efficient work tools. Our research aimed at identifying the perception of students from the Faculty of Economics and Business Administration (FEAA), which belongs to “Alexandru Ioan Cuza” University of Iaşi, concerning the utility and degree of acceptance of the new e-learning methods. We try to analyze the degree of opposition in adopting them, the limits and motivations, the preference for a certain type of teaching-learning (usual, e-learning, mixed), as well as at finding out the way in which students perceive the assessment of their knowledge by using the new information technologies. The research demonstrates that there are significant differences between what is required and what is expected on a theoretical level from the new educational systems as well as the way in which they are accepted and used by students in practice. The main identified barrier is the students' reluctance towards the new learning methods due, in our opinion, to the human opposition to change on the one hand and on the other hand to the lack of information about its advantages. We consider appropriate expanding research topic article to the other universities in the country in order to understand the impact of current e-learning as a whole, at national level.
Keywords: A22; A23; O33; 330; e-Learning; the knowledge technology; e-universities; students; communication; virtual; education